Pengaruh Sistem Informasi Akuntansi dan Pemanfaatan Teknologi Informasi terhadap Kinerja Karyawan di Indonesia - Nuriani Nuriani; Rayyan Firdaus (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
In the modern era, the implementation of Accounting Information Systems (AIS) and the use of Information Technology (IT) have an impact on employee performance in Indonesia. This research investigates various relevant previous studies through a thorough literature study. The results show that AIS and IT improve employee performance. The combination of the two can improve productivity, product or service quality, and a company's competitive advantage; AIS can improve work efficiency, data accuracy, and decision-making quality, while IT enables better collaboration, work flexibility, and wider information access. But the success of AIS and IT depends on many things, such as management support, employee training, and the suitability of the system to business needs. According to this study, AIS and IT are important components in improving employee performance in Indonesia.